ANALISIS PENGENDALIAN PERSEDIAAN BAHAN BAKU DENGAN MENGGUNAKAN METODE MATERIAL REQUIREMENT PLANNING PADA PT ATMI DUTA ENGINEERING - Muh. Qoyyum Mahfudhon, Amin Wahyudi & Erni Widajanti (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2018)
The purpose of this research is to analyze the raw material needs planning policyimplemented by ATMI PT Duta Engineering. Analyzing the application of the method ofMaterial Requirements Planning can play a role in optimizing raw material inventorycontrol at PT Duta ATMI Engineering. Analytical techniques used in this research is byusing the method of MRP (Material Requirements Planning). The research resultsobtained conclusions planning needs raw materials policy implemented by ATMI PTDuta Engineering yet structured, it is apparent from the raw material procurementsystem which uses a method of forecasting in accordance with sales targets. Applicationof the method of Material Requirements Planning can play a role in mengoptimumkanraw material inventory control at PT Duta ATMI Engineering, it is shown in the totalcost of the inventory using the technique of Lot For Lot (LFL) is Rp 15,443,120, the totalcost of the inventory using the technique of Fixed Order Quantity amounting to Rp13,277,760 and the total cost of the inventory using the policy of the company amountingto Rp 50,754,720. From the comparison it can be noted that a very effective technique toachieve cost-efficiency the total inventory of raw materials is the technique of FixedOrder Quantity.Keywords: need raw materials, Material Requirements Planning.